1985
DOI: 10.1007/bf00199230
|View full text |Cite
|
Sign up to set email alerts
|

DR antigens expressed on tumor cells do not contribute to the blastogenetic response of autologous T cells

Abstract: Tumor cell suspensions prepared from surgical specimens were characterized for cellular composition and reactivity with monoclonal antibodies detecting T lymphocytes, monocytes, and the monomorphic determinants of DR molecules (antigens encoded by the D region of the major histocompatibility complex in man). About half the adenocarcinoma preparations contained tumor cells which expressed DR antigens. Lymphocytes of certain patients were stimulated in vitro by the autologous tumor cells, and this was independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…A role for class II antigens, especially DR, emerges from our studies which suggest that DR expressed on Me cells can regulate both positively and negatively the cellular immune response of the patients. These data seem to be confirmed by some studies (51) but not by others (91). It is important to further define the function of DR molecules in the regulation of the immune interactions between the tumor and the host and to identify which molecule (DR DC, SB) and epitopes may have such regulatory function.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A role for class II antigens, especially DR, emerges from our studies which suggest that DR expressed on Me cells can regulate both positively and negatively the cellular immune response of the patients. These data seem to be confirmed by some studies (51) but not by others (91). It is important to further define the function of DR molecules in the regulation of the immune interactions between the tumor and the host and to identify which molecule (DR DC, SB) and epitopes may have such regulatory function.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, these authors stressed the correlation between DR expression and positive MLTC by using FACS-isolated DR+ cells, which did stimulate much more than DR-cells derived from the same Me cell population. However, other recent results did not support a positive correlation between the expression of DR antigens on human tumors of different histology and autologous MLTC (91).…”
Section: A Correlation Between Class H Antigens Expression On Primarmentioning
confidence: 62%
“…Nevertheless the induction of lymphocyte proliferation and cytotoxicity has to date proved useful in identifying cross-reacting antigens in human neoplasms and in the disclosure of effector cells with variable target cell repertoires [31]. Moreover, there is a correlation between lymphocyte-mediated auto-tumour reactivity and clinical course [29,30].…”
Section: Introductionmentioning
confidence: 97%
“…We have previously reported that tumour-associated T cells proliferate vigorously in response to autologous non-T cells in cancer patients with malignant pleural effusions [17]. However, the reactions observed in the autologous MLTC are unlikely to result from auto-recognition of HLA-DR antigens, since neither the proliferative response [30] nor development of auto-tumour cytotoxicity was blocked by monoclonal antibodies against HLA-DR antigens (unpublished observation). Furthermore, positive autologous MLTC reactions were recorded irrespective of the expression of class I and class II major histocompatibility (MHC) antigens on effusion tumour cells (data not shown).…”
Section: Discussionmentioning
confidence: 82%